Status Kewarganegaraan Pengungsi dan Pencari Suaka: (Tinjauan Komparatif antara Konvensi Internasional dan Hukum Nasional Indonesia) - Fathoni Abdulfalih; Muhammad Yasykur Ibadurrahman; Jamaluddin Ahmad; Abdillah Azzam Ramadhan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The refugee and asylum seeker phenomenon raises complex legal issues, especially concerning their citizenship status and international legal protection. Many refugees face statelessness, which requires legal safeguards under international instruments such as the 1951 Refugee Convention and the 1967 Protocol. However, Indonesia has not ratified the 1951 Convention, relying instead on Presidential Regulation No. 125 of 2016. This study aims to compare the citizenship status of refugees and asylum seekers under international law and Indonesian national law. The research employs a normative legal method with a comparative approach by examining legal instruments, academic journals, and literature. The results show that international law provides broader protection, while Indonesian national law is limited to administrative and humanitarian aspects without granting permanent citizenship. In conclusion, there exists a normative gap between international conventions and Indonesian legal policies, requiring harmonization to ensure adequate protection for refugees and asylum seekers.